A Tiszai vízjárás változások valószínű okai - Gönczy Sándor; Генці Шандор; Molnár József; Молнар Йосип (Erdélyi Magyar Műszaki Tudományos Társaság – EMT, 2004)
Kárpátalján az utóbbi években két alkalommal, 1998 novemberében és 2001 márciusában katasztrofális méretű árhullámok pusztítottak. A Felső-Tiszán levonuló árhullámok gyakoriság-változásainak, illetve ezek okainak feltárására kezdtünk kutatásokat az Arany János Közalapítvány támogatásával. Az árvizek, illetve a folyók mederváltozásaival szembeni védekezés történhet passzívan és aktívan (MIKE, 1991). A fejletlen társadalmak települései passzív védekezésként kitérnek a meanderező folyó útjából. Az aktív védekezés a folyók szabályozása, gátak közé szorítása.

Abstract. The control of the Tisza from the 18th century significantly changed the flood plains along the river, its ecology, hydrology, load transport and the bed development. The unexpected huge floods of the river in recent years underlined the searching the reasons in the area of the Upper-Tisza and especially Subcarpathia. The research carried out by the authors involved the examination of the effects of aforestation, the analysis of the runoff and the characteristics of the drainage basin and the modelling of the infill and sedimentation along the river in Subcarpathia. The results prove that the effects of a forestation are less than it was suggested. The infill of the flood plain of the dammed section between Nagysz(l(s (Vinogradov) and Tiszaújlak (Vilok) is found to be 29,1 cm for 38-km2 total areas. The authors also found that the intensively infilling parts significantly impound the river without dredging and bed alignment.
Fluctuațiile debitelor şi cauze probabile ale acestora pe râul Tisza
Possible causes of fluctuations in the water level of the Tisza river
Teljes kiadvány: https://emt.ro/sites/default/files/archivum/2017-12/msz25.pdf
Keywords: Tisza; vízjárás; Nagyszőlős; Tiszaújlak; Kárpátalja